(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Biogas has evolved as a viable renewable energy conversion technology for agricultural, animal, industrial, and municipal wastes. Biogas development may be employed alongside sanitation and indoor air pollution reduction efforts to lower greenhouse gas emissions. In India, total biogas production is presently 2.07 billion m3 per year. This is tiny in contrast to its potential, which is predicted to reach between 29 and 48 billion m3 per year. As a consequence, the purpose of this study is to identify both technical and non-technical hurdles to biogas adoption in India. The expansion of biogas is affected by a range of waste, renewable energy, and local restrictions. Decomposition analysis was utilized to identify particular constraints for rural and urban biogas systems that exist in India. Because of variances in technical progress, feedstock availability and quality, supply chain, awareness level, and governmental assistance, the sort and magnitude of hurdles vary greatly throughout biogas systems.